2006
DOI: 10.1507/endocrj.53.147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a 1 step TRAb Assay for the Detection of High-affinity Components to hTSHR: Evidences Indicating Superiority of the Assay in the Lower TRAb Range

Abstract: Abstract. The aim of this study was to develop an assay to selectively detect high-affinity components among TRAb. Using an rhTSHR-coated tube system, a 1 step TRAb assay method was developed that included 1) co-incubation with 125 I-bTSH, 2) a 50 ml serum sample, 3) an increased incubation volume (450 ml), and 4) a 1 hour incubation time. Sixtyone TRAb positive Graves' sera were studied. When the regular TRAb assay (Reg) results were quantitatively compared to the 1 step assay (1 step) results, certain disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…As a fact, the three GD a patients with discrepant TRAb values showed low TRAb levels by the two-step TRAb RIA (< 2 IU/L). A similar phenomenon was reported by comparison of a 2 nd generation TRAb assay using 125 I-labelled bovine TSH for the inhibition of patient TRAb to solid-phase immobilized human TSHR in a simultaneous reaction environment with its corresponding consecutive assay 9 21 They concluded that the one-step TRAb assay detected particularly biologically active TRAb in patients with low TRAb levels. In contrast, the consecutive TRAb assay presumably also identified low affinity TRAb that lack thyroid stimulatory activity and did not reflect clinical symptoms.…”
Section: Discussionsupporting
confidence: 71%
“…As a fact, the three GD a patients with discrepant TRAb values showed low TRAb levels by the two-step TRAb RIA (< 2 IU/L). A similar phenomenon was reported by comparison of a 2 nd generation TRAb assay using 125 I-labelled bovine TSH for the inhibition of patient TRAb to solid-phase immobilized human TSHR in a simultaneous reaction environment with its corresponding consecutive assay 9 21 They concluded that the one-step TRAb assay detected particularly biologically active TRAb in patients with low TRAb levels. In contrast, the consecutive TRAb assay presumably also identified low affinity TRAb that lack thyroid stimulatory activity and did not reflect clinical symptoms.…”
Section: Discussionsupporting
confidence: 71%